Affection and Healthy Housing: A Reflection about the House in Covid-19 Pandemic (Global Journal of Human-Social Science, 2020)
The mandatory domestic reclusion during the COVID-19 pandemic enabled a unique space experience. The home's welcoming space became a citadel for the invisible enemy's protection, COVID-19. Using the rhizomatic methodological approach of Deleuze and Guattari through the cartography practice about forces and affections, he recognized the crossing flow's forces and affections agency by the bodies (human and architectural), identifying lines of action and lines of scapes, to imagine the post context -pandemic in promoting health for healthier housings with the construction of healthy environments. When thinking about contamination, making the difference notorious and weaving into the open fissures and gaps in the lived spatial experience enables the creation of other territories stimulating healthy environments to enhance healthy housing. In the same way, when inhabiting the "rhizome house", it activated connections with the subjective city of the post-pandemic, in addition to the functionality enabling the resingularization of meetings and disagreements in the public space and enhancing healthy housing in the shared construction of a healthy city.
Keywords: healthy city; healthy housing; Covid-19; cartography; rhizome; affections